Integrative approach for optimizing construction and demolition waste management practices in developing countries - Abeer Abulebdah; Farayi Musharavati; Enas Fares (Sustainable Environment, 2024)
Due to the numerous infrastructure development projects taking place in developing nations, large amounts of construction and demolition waste (C&DW) are unavoidable. Most C&DW management strategies, however, involve ‘isolated’ operations with high overhead. Waste data transfers are difficult to watch over. Important information needed for decision-making is, therefore, challenging to obtain. This paper’s goal is to discuss C&DW management from an integrative standpoint. Using GIS functions and a fuzzy analytical hierarchy approach, the best sites for waste management facilities can be found. A mixed integer optimization model is created to identify optimal location and allocation of waste management facilities. The objective is to reduce waste collection costs under different operational scenarios. By incorporating ‘constructs elements’ and ‘connected elements’ that are linked, isolated C&DW management ventures are transformed into successful C&DW management ventures. The effectiveness and efficiency of waste management strategies are evaluated using GIS analysis. A dashboard for tracking waste data flows is created to show how stakeholder decision making can be made easier. The proposed integrative approach differs from other approaches since it re-purposes location-allocation models and GIS data to optimize ‘isolated’ C&DW management practices. In addition, the notion of ‘construct elements’ that can be time-shared is outlined. Moreover, the notion of ‘connected elements’ that are dynamic, time-limited, and yet transient enough to provide the necessary interconnectivity is developed to support and complement the seamless function of a network of C&DW management facilities. The usefulness of the integrative approach is illustrated by a case study. Analysis of case studies demonstrates that waste management strategies in developing countries can be made more effective and waste collection efficiency can be increased. According to comparative studies, updating current waste management facilities can cut operating costs by 26%, while implementing an integrative strategy can cut costs by 52%. The discussions in this paper can help towns reevaluate C&DW management and put useful, unified C&DW management techniques into practice.